EMPOWERING HIGHER EDUCATION: INSTITUTIONAL PERFORMANCE AS A KEY FACTOR - Nur Hayati; Dani Sopian; Arief Yanto Rukmana (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
One of the industries that is expanding is higher education, and it is seeing more and more competition. Strong leadership and the use of artificial intelligence technologies are viewed as the keys to raising higher education's effectiveness and competitiveness. In order to better understand how leadership, artificial intelligence, and higher education technology work together to improve higher education's competitive advantage, this study examines the relationships between artificial intelligence, leadership, and higher education competitiveness. It also takes into account the potential influence of higher education's performance as moderation. Using a sample of 250 students from five private higher education institutions in Bandung that provide recognized B Management study programs, this study employed the Purposive Sampling approach. SEM PLS (Partial Least Square) is the approach used for data analysis in this study. The findings demonstrate a strong, direct, and beneficial relationship between leadership and artificial intelligence and the effectiveness and competitiveness of higher education. It is anticipated that the study's conclusions will offer executives, employees, and practitioners in higher education insightful information. Finding the important variables that influence the competitiveness of higher education, such as the ways in which artificial intelligence and good leadership can work together, can help with strategic decision-making for the growth of long-lasting institutions.